Acute arsine poisoning after exposure on cleaning an industrial purifier at a family-run workshop - Zou, Hua; Zhang, Meibian; Xue, Panqi; Wei, Fang; Li, Fei; Fang, Xinglin; Lou, Xiaoming; Zhou, Lifang (Frontiers in Public Health, 2025)
We report a rare incident of acute arsine poisoning when cleaning an industrial purifier to enhance awareness for the prevention of arsine poisoning incidents in the family-run workshop. In this incident, three workers of a family-run cleaning workshop developed symptoms of headache, abdominal pain, chills, fatigue, and hematuria after cleaning an industrial purifier, with a latency period 4–6 h after exposure. Field investigations and laboratory tests were used to investigate the poisoning incident. Red blood cell counts and levels of hemoglobin, alanine transaminase, and urinary arsenic (As) increased, and urinary protein and occult blood tests indicated strongly positive results. The cleaning workshop undertook no effective measures to prevent occupational poisoning. The As concentration in flame retardants, dust on the surface of the industrial purifier, and water in the soaking pool was 269 mg/kg, 1.72 × 105 mg/kg, and 6.89 × 103 mg/L, respectively. This incident highlighted the association of the acute arsine poisoning during the cleaning of an industrial purifier with poor occupational health management practices. Effective measures for the prevention of the acute poisoning should therefore be undertaken.